2021
DOI: 10.3390/vaccines9050443
|View full text |Cite
|
Sign up to set email alerts
|

Confidence, Acceptance and Willingness to Pay for the COVID-19 Vaccine among Migrants in Shanghai, China: A Cross-Sectional Study

Abstract: Understanding the public’s attitude towards COVID-19 vaccination and their acceptance could help facilitate the COVID-19 rollout. This study aimed to assess the acceptance and willingness to pay (WTP) for the COVID-19 vaccine among migrants in Shanghai, China. A cross-sectional study was conducted among 2126 migrants in Shanghai for the period 1–20 November 2020. Convenience sampling was used to recruit respondents in workplaces with large numbers of migrant workers. Multivariable (ordered) logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 37 publications
6
43
2
Order By: Relevance
“…Apart from the demographic and HBM factors, we also identified several COVID-19 specific predictors in this study. Parallel to other studies [ 20 , 24 , 27 , 34 ], this study reveals a negative association between concern about vaccine safety and intention to receive the vaccine. That is, the more an individual is concerned about the safety issues, the less likely he or she will receive the vaccine.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Apart from the demographic and HBM factors, we also identified several COVID-19 specific predictors in this study. Parallel to other studies [ 20 , 24 , 27 , 34 ], this study reveals a negative association between concern about vaccine safety and intention to receive the vaccine. That is, the more an individual is concerned about the safety issues, the less likely he or she will receive the vaccine.…”
Section: Discussionsupporting
confidence: 81%
“…Even when we compared the rates within the Chinese population, intention to receive COVID-19 vaccines in Hong Kong is among the bottom. Previous studies have found that 89–92% of individuals in China were willing to get vaccinated once the vaccines are available [ 34 , 35 ]. Our findings suggest possible discrepancies within a large population of the same ethnicity, and that low vaccination intention may not be an issue solely due to cultural reasons.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional, web-based, anonymous survey was conducted among cancer patients in Eastern China, from June 17th to September 3rd, 2021. The study was conducted using the “Questionnaire Star,” a paid website that helps generate, distribute, and retrieve electronic questionnaires for mobile platforms [44] . Cancer patients over the age of 18 years were invited to participate in the study, and those with cognitive disabilities were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The self-report questionnaire was developed to assess knowledge about the COVID-19 vaccine, attitude towards the vaccine and acceptance of the vaccine, following a review of similar studies previously published in the scientific literature [30] , [44] , [45] , [46] , [47] , [48] , [49] . The questionnaire was developed in English and then translated into Chinese.…”
Section: Methodsmentioning
confidence: 99%
“…The willingness to pay for vaccination is linked to vaccine acceptance. It has been reported in previous studies that vaccine price was significantly associated with vaccine acceptance [ 30 , 31 ]. Pakistan is a lower-middle-income country, where almost 35% of the population lives beneath the poverty line [ 32 ].…”
Section: Introductionmentioning
confidence: 99%